EFEKTIVITAS PENERAPAN APLIKASI PAK CAMAT DALAM PELAYANAN ADMINISTRASI DI KECAMATAN BUKIT RAYA KOTA PEKANBARU TAHUN 2023 - Risya, Wiyoke Ananda; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Government of Pekanbaru City, through the Bukit Raya Subdistrict, developed a digital service innovation called the Pak Camat application. This application was created to support the implementation of Law No. 25 of 2009 on Public Services, Presidential Instruction No. 3 of 2003 on the Development of E-Government, and Pekanbaru Mayor Regulation No. 13 of 2023 on Electronic-Based Government Systems. However, in its implementation, several challenges have been identified, such as the lack of competent human resources, insufficient outreach from the subdistrict office, and low digital literacy among the public. This study aims to examine the effectiveness of the Pak Camat application in delivering administrative services at Bukit Raya Subdistrict in 2023. The research employs a descriptive qualitative approach, using data collection techniques such as interviews and documentation. The types of data used are primary and secondary data. Primary data were obtained through interviews with informants, while secondary data were gathered from supporting documents relevant to the study. The results of the study show that Pekanbaru Mayor Regulation (Perwako) No. 13 of 2023 aims to improve public services through the use of technology. However, in practice, there are still several obstacles, including a lack of competent human resources, limited outreach from the subdistrict office, and low digital literacy among the community. Nevertheless, the application has succeeded in increasing the number of administrative services and supports public service delivery that is transparent and flexible. The implementation of the Pak Camat application is considered to be in line with e-government principles, but improvements are needed in terms of increasing public outreach by the Bukit Raya Subdistrict to ensure that the application can be optimally utilized by all segments of society. Keywords: Implementation, Pak Camat Application, Administrative Servic.